The experiences of students with intellectual and developmental disabilities, parents, and teachers regarding health self-advocacy program with school-home connection: a qualitative study - Lee, Suk-Hyang; Kang, Ha-Nul; Kim, Soyeon (Frontiers in Psychiatry, 2023)
Background: Despite the importance of health as a significant indicator of quality of life, individuals with intellectual and developmental disabilities (IDD) often face low expectations, stigma, and insufficient opportunities in health care and education. In response, we developed a health self-advocacy program with a school-home connection for students with IDD to promote self-directed health care and verified its effectiveness by implementing the program for students with IDD. Objective: This study aimed to explore participants’ program experiences and support needs to reduce the stigma surrounding individuals with IDD and provide implications for enhancing health self-advocacy skills. Methods: Individual and focus group interviews were conducted with 14 students, six parents, and four teachers who participated in the program. The collected data were analyzed using the constant comparative method. Results: The following five main themes emerged: a) the gap between perception and practice in health care; b) advantages and influencing factors of the program; c) challenges in program implementation; d) outcomes of program implementation; and e) support needs for promoting health self-advocacy. Conclusions: Based on these findings, implications are provided and discussed to reduce the stigma surrounding individuals with IDD and enhance health self-advocacy.